Table of Contents
Last modified on January 30th, 2025
Inverse trigonometric identities are mathematical relationships that involve the inverse trigonometric functions: arcsine (sin-1), arccosine (cos-1), arctangent (tan-1), arccosecant (cosec-1), arcsecant (sec-1), and arccotangent (cot-1). These functions determine the angles (or arcs) corresponding to given trigonometric ratios.
Here is the list of all the inverse trigonometric identities and their types.
A trigonometric function and its inverse cancel each other out, returning the original input within a specific range. These identities explain how trigonometric functions interact with their inverses.
Similarly, for inverse functions applied to trigonometric values:
Negative identities describe how inverse trigonometric functions behave when their input is negative. Some functions return a simple negation, while others involve a transformation using π:
For sine, tangent, and cosecant functions, a negative input results in the negation of the function’s value:
For cosine, secant, and cotangent functions, the transformation involves subtracting the inverse function’s value from π, ensuring the result remains within the principal range:
Reciprocal identities establish direct relationships between inverse trigonometric functions and their reciprocal counterparts:
The sum of two complementary inverse trigonometric functions always results in a constant value of ${\dfrac{\pi }{2}}$:
These identities are used where two inverse tangent functions are added or subtracted:
These relate inverse trigonometric functions to double angles:
Here is a summary of all the identities.
We will now use the above identities to solve or simplify some expressions involving inverse trigonometric functions.
Simplify: sin-1 x – sin-1(-x)
Given, sin-1 x – sin-1(-x) …..(i)
First, we identify the identity which is needed to simplify the given expression. Here, we will use the negative identity of inverse sine functions.
As we know, sin-1(-x) = -sin-1 x
Here, from (i), we get
= sin-1 x – (-sin-1 x)
= sin-1 x + sin-1 x
= 2 sin-1 x
Evaluate: tan(tan-1 5)
Given, tan(tan-1 5) …..(i)
First, we identify the identity which is needed to simplify the given expression. Here, we will use the basic identity of inverse sine functions.
As we know, tan(tan-1 x) = x
Here, from (i), we get
= 5
Now, let us prove a few inverse trigonometric identities.
Let y = sin-1(sinx)
⇒ sin y = sin x
Since the range of the inverse sine function is ${\left[ -\dfrac{\pi }{2},\dfrac{\pi }{2}\right]}$, y must lie in this interval.
Thus, ${-\dfrac{\pi }{2}\leq y\leq \dfrac{\pi }{2}}$
⇒ y = x
⇒ sin-1(sinx) = x
Thus, sin-1(sin x) = x, for x ∈ ${\left[ -\dfrac{\pi }{2},\dfrac{\pi }{2}\right]}$
Let sin-1(-x) = y
⇒ -x = sin y
⇒ x = -sin y
⇒ x = sin(-y)
⇒ sin-1 x = sin-1(sin(-y))
⇒ sin-1 x = -y
⇒ -sin-1 x = y
⇒ -sin-1 x = sin-1(-x)
Thus, sin-1(-x) = -sin-1 x, for x ∈ [-1, 1]
Let cos-1(-x) = y
⇒ -x = cos y
⇒ x = -cos y
Since cos(π – q) = -cos q
⇒ x = cos(π – y)
⇒ cos-1 x = π – y
⇒ cos-1 x = π – cos-1(-x)
⇒ cos-1(-x) = π – cos-1 x
Thus, cos-1(-x) = π – cos-1 x, for x ∈ [-1, 1]
Let cosec-1 x = y
⇒ x = cosec y
⇒ ${\dfrac{1}{x}=\sin y}$
⇒ ${\sin ^{-1}\left( \dfrac{1}{x}\right)}$ = y
⇒ ${\sin ^{-1}\left( \dfrac{1}{x}\right)}$ = ${\text{cosec}\, ^{-1}x}$
Thus, ${\sin ^{-1}\left( \dfrac{1}{x}\right) =\text{cosec}\, ^{-1}x}$, for x ≥ 1 or x ≤ -1
Let sin-1 x = y
⇒ x = sin y
⇒ x = ${\cos \left( \dfrac{\pi }{2}-y\right)}$
⇒ cos-1 x = ${\cos ^{-1}\left( \cos \left( \dfrac{\pi }{2}-y\right) \right)}$
⇒ cos-1 x = ${\dfrac{\pi }{2}-y}$
⇒ cos-1 x = ${\dfrac{\pi }{2}}$ – sin-1 x
⇒ sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$
Thus, sin-1 x + cos-1 x = ${\dfrac{\pi }{2}}$, for x ∈ [-1, 1]
Let tan-1 x = A and tan-1 y = B
⇒ x = tan A and y = tan B
Since tan(A + B) = ${\dfrac{\tan A+\tan B}{1-\tan A\tan B}}$
⇒ tan(A + B) = ${\dfrac{x+y}{1-xy}}$
⇒ A + B = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$
⇒ tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$
Thus, tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$, for xy < 1
Let tan-1 x = y
⇒ x = tan y
Now, R.H.S. = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$
= ${\sin ^{-1}\left( \dfrac{2\tan y}{1+\tan ^{2}y}\right)}$
Since sin 2θ = ${\dfrac{2\tan \theta }{1+\tan ^{2}\theta }}$
= ${\sin ^{-1}\left( \sin 2y\right)}$
= 2y
= 2 tan-1 x = L.H.S.
Thus, 2 tan-1 x = ${\sin ^{-1}\left( \dfrac{2x}{1+x^{2}}\right)}$, for |x| ≤ 1
Prove: tan1 1 + tan-1 2 = -tan-1 3
As we know, the sum identity is:
tan-1 x + tan-1 y = ${\tan ^{-1}\left( \dfrac{x+y}{1-xy}\right)}$, for xy < 1
Substituting x = 1 and y = 2,
tan-1 1 + tan-1 2
= ${\tan ^{-1}\left( \dfrac{1+2}{1-1\times 2}\right)}$
= tan-1(-3)
= -tan-1 3
Prove: ${\cos ^{-1}x=\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$
Let cos-1 x = y
⇒ x = cos y
Then, sin y = ${\sqrt{1-x^{2}}}$
⇒ cosec y = ${\dfrac{1}{\sqrt{1-x^{2}}}}$
⇒ y = ${\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$
Since y = cos-1 x
⇒ cos-1 x = ${\text{cosec}\, ^{-1}\dfrac{1}{\sqrt{1-x^{2}}}}$
Evaluate: sin(tan-1 3)
Let y = tan-1 3
⇒ tan y = 3
Given, sin(tan-1 3)
= sin y
Since tan y = 3 = ${\dfrac{Opposite}{Adjacent}}$
Opposite = 3 and adjacent = 1
Thus, hypotenuse = ${\sqrt{3^{2}+1^{2}}}$ = ${\sqrt{10}}$
Here, sin y = ${\dfrac{Opposite}{Hypotenuse}}$ = ${\dfrac{3}{\sqrt{10}}}$
⇒ sin(tan-1 3) = ${\dfrac{3}{\sqrt{10}}}$
Solve for x: ${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\tan ^{-1}x}$, x > 0
Given, ${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\tan ^{-1}x}$
Let tan-1 x = y
⇒ x = tan y
Rewriting the equation using substitution,
${\tan ^{-1}\left( \dfrac{1-x}{1+x}\right) =\dfrac{1}{2}\theta}$
⇒ ${\tan \left( \tan ^{-1}\left( \dfrac{1-x}{1+x}\right) \right) =\tan \left( \dfrac{\theta }{2}\right)}$
⇒ ${\dfrac{1-x}{1+x}=\tan \left( \dfrac{\theta }{2}\right)}$
Since ${\tan \left( \dfrac{\theta }{2}\right) =\dfrac{\sin \theta }{1+\cos \theta }}$
Also, deriving from the triangle representation of tan y = x,
sin y = ${\dfrac{2x}{1+x^{2}}}$ and cos y = ${\dfrac{1-x^{2}}{1+x^{2}}}$
Here, ${\dfrac{1-x}{1+x}=\dfrac{\dfrac{2x}{1+x^{2}}}{1+\dfrac{1-x^{2}}{1+x^{2}}}}$
⇒ ${\dfrac{1-x}{1+x}=x}$
⇒ 1 – x = x + x2
⇒ x2 + 2x – 1 = 0
⇒ x = ${\dfrac{-2\pm \sqrt{\left( 2\right) ^{2}-4\left( 1\right) \left( -1\right) }}{2\left( 1\right) }}$
⇒ x = ${-1\pm \sqrt{2}}$
Since x > 0
Thus, x = ${\sqrt{2}-1}$
Last modified on January 30th, 2025